Visceral Fat, Waist Circumference, and BMI: Impact of Race/ethnicity - Carroll, Joan F.; Chiapa, Ana L.; Rodriquez, Mayra; Phelps, David R.; Cardarelli, Kathryn M.; Vishwanatha, Jamboor K.; Bae, Sejong; Cardarelli, Roberto (Obesity (Silver Spring, Md.), 2008)
Objective: BMI and waist circumference are used to define risk from excess body fat. Limited data in women suggest that there may be racial/ethnic differences in visceral adipose tissue (VAT) at a given BMI or waist circumference. This study tested the hypothesis that racial/ethnic differences exist in both men and women in the relationship of anthropometric measures of body composition and computed tomography (CT)‐determined VAT or subcutaneous adipose tissue (SAT). Methods and Procedures: Subjects included 66 African American, 72 Hispanic, and 47 white men and women, aged ≥45. Waist circumference and BMI were measured using standard methods. Total abdominal and L4L5 VAT and SAT were measured using CT. Results: Among both men and women, groups did not differ in waist circumference or BMI. White men had greater L4L5 VAT than African‐American men, and both white and Hispanic men had greater total VAT than African‐American men. Among women, Hispanics and whites had greater L4L5 VAT than African Americans, and Hispanics had greater total VAT than African Americans. The slope of the linear relationship between BMI or waist circumference and VAT was lower in African Americans than in Hispanics and/or whites. Discussion: Middle‐aged and older African‐American men and women had lower VAT despite similar BMI and waist circumference measurements. Altered relationships between anthropometric measures and VAT may have implications for defining metabolic risk in different populations. Different waist circumference or BMI cutoff points may be necessary to adequately reflect risk in different racial/ethnic groups.